Fundamental statistics for the behavioral sciences - Howell, David C. (Wadsworth, Cengage Learning, 2014)
Designed as an introductory statistics course in psychology, education, and other behavioral sciences, emphasizing the logic of statistical procedures and interpretation of data rather than computational derivations.